Hypothalamic functional MRI activity in the initiation phase of spontaneous and glyceryl trinitrate‐induced migraine attacks. (14th July 2021) - van Oosterhout, Willebrordus P. J.; van Opstal, Anne M.; Schoonman, Guus G.; van der Grond, Jeroen; Terwindt, Gisela M.; Ferrari, Michel D.; Kruit, Mark C.
Abstract: The hypothalamus has been suggested to be important in the initiation cascade of migraine attacks based on clinical and biochemical observations. Previous imaging studies could not disentangle the changes due to the attack and those due to the trigger compound. With a novel approach, we assessed hypothalamic neuronal activity in early premonitory phases of glyceryl‐trinitrate (GTN)‐induced and spontaneous migraine attacks. We measured the hypothalamic blood oxygen level‐dependent (BOLD) response to oral glucose ingestion with 3T‐functional magnetic resonance imaging (MRI) in 27 women, 16 with migraine without aura and 11 controls group matched for age and body mass index (BMI), on 1 day without prior GTN administration and on a second day after GTN administration (to coincide with the premonitory phase of an induced attack). Interestingly, subgroups of patients with and without GTN‐triggered attacks could be compared. Additionally, five migraineurs were investigated in a spontaneous premonitory phase. Linear mixed models were used to study between‐ and within‐group effects. Without prior GTN infusion, the BOLD response to glucose was similar in migraine participants and controls ( P  = .41). After prior GTN infusion, recovery occurred steeper and faster in migraineurs (versus Day 1; P  < .0001) and in those who developed an attack versus those who did not ( P  < .0001). Prior GTN infusion did not alter the glucose‐induced response in controls (versus baseline; P  = .71). Just before spontaneous attacks, the BOLD‐response recovery was also faster ( P  < .0001). In this study, we found new and direct evidence of altered hypothalamic neuronal function in the immediate preclinical phase of both GTN‐provoked and spontaneous migraine attacks. Abstract : Recent data suggest that the hypothalamus is important in the initiation cascade of migraine attacks based on clinical and biochemical observations. Here, we found new and direct evidence of altered hypothalamic neuronal function in the immediate preclinical phase of both GTN‐provoked and spontaneous migraine attack. The hypothalamic blood oxygen level‐dependent (BOLD) response to oral glucose ingestion after overnight fasting was measured with 3T‐functional MRI in women with migraine and nonmigraine controls at three time points. At baseline, there was no difference in the response between patients and controls: a normal, persisting drop in BOLD signal reflecting reduced neuronal metabolic activity in the lateral hypothalamic area where glucosensitive neurons are located. Both at the beginning of GTN‐provoked migraine attacks and at the beginning of spontaneous attacks, this BOLD response was steeper (vs. baseline) in the patient group reflecting an unresponsiveness to the glucose ingestion. These findings imply a migraine‐attack related disturbance of normal hypothalamic functioning: a disinhibited hypothalamic satisfaction. This abnormal response seems attack‐specific, as it was not found in the control group nor in the migraine.